The Female Body as the Site of Male Violence during the Partition of India in Bapsi Sidhwa’s "Ice-Candy-Man" - Dey, Arunima (Complutense Journal of English Studies, 2018)
This paper on Bapsi Sidhwa’s Ice-Candy-Man intends to undertake a comprehensive investigation of various forms of gendered violence during the partition of India. An analysis of the central female figure of Ayah underscores how acts of abduction and rape use woman’s sexuality as a tool to articulate religious/national enmity. Moreover, the paper will claim that Ayah’s abduction can be read as a punishment for her lack of adherence to cultural norms, which was expected from women during partition period, thereby highlighting that women’s bodies were (and continue to be) under patriarchal surveillance and regulation, and those who fail to abide by societal rules are inevitably discarded. Next, I intend to explore the effective use of female agency and solidarity in the novel as a means to counter male violence and subjugation. Furthermore, I will comment on the treatment of abducted/raped women by the patriarchal state to expose the social reality post partition where victimised women, due to their altered position as contaminated sexual beings, were ostracised by society. In essence, by investigating gendered violence during partition followed by continued societal victimisation of the female survivors, this paper will highlight how Sidhwa’s novel contributes to a thus far silenced gynocentric reading of partition history.